Acupuncture and related therapies for stress urinary incontinence: A protocol for systematic review and network meta-analysis. Issue 28 (10th July 2020) - Yang, Jiao; Cheng, Ying; Zhao, Ling; Chen, Jiao; Zheng, Qianhua; Guo, Yaoguang; Liang, Fanrong
Abstract: Background: Stress urinary incontinence (SUI) is the most common type of urinary incontinence, affecting patients' quality of life and sexual function. Lots of Clinical trials suggested that acupuncture is beneficial for SUI and various acupuncture methods have been widely used in clinic. However, the comparative efficacy and safety of these acupuncture methods remains unclear. Clinicians are confused to select the optimal way to treat SUI. This review aims to gather solid evidence in order to provide reliable reference in establishing guidelines for acupuncture treatment of SUI. Methods: Relevant databases including MEDLINE, Cochrane Library, EMBASE, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, Wanfang Database, the Chongqing VIP Chinese Science and Technology Periodical Database will be retrieved from their inception to April 2020. The quality of the included studies will be evaluated by the risk of bias tool and the evidence will be evaluated by Grading of Recommendations Assessment, Development and Evaluation System. Network meta-analysis will be conducted by using software R3.5.1. The primary outcome is the number of patients with self-reported continence and number of patients with self-reported improvement in SUI. Results: The results of this network meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: the results may be useful for patients, clinicians, and guideline-makers to choose the optimal acupuncture method for SUI treatment.